Revocation of Art. 305 of the Military Criminal Process Code in front of the Constitutional Guarantee of the right to silence - Guimarães Teixeira Rocha, Maria Elizabeth (REVISTA ELECTRONICA IBEROAMERICANA, 2022)
-